Internalisasi Nilai Budaya melalui Tari Tradisional Kreasi Batik dalam Pembelajaran Sekolah Dasar - Aldy Ferdiyansyah; Bagus Aulia Iskandar (Journal of Character and ELementary Education, 2026)
This study aims to describe the process of internalizing cultural values through traditional batik dance creations in learning in fifth graders of SDN Tulusrejo 2 with a focus on the introduction of cultural values through symbols and dance movements, contextual learning experiences, student interactions in dance activities, and the role of teachers in directing the meaning of learning. This study uses a qualitative approach with a descriptive design. The research subjects consisted of 10 fifth grade students and one class teacher. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the internalization of cultural values takes place through the introduction of batik symbols connected to dance movements, learning experiences through direct practice, and the formation of values such as cooperation, responsibility, and discipline through group interactions during learning, while the teacher acts as a facilitator who directs and gives meaning to each activity. The conclusion of the study shows that the internalization of cultural values through traditional batik dance creations occurs through a series of learning experiences that include cultural symbols, dance practices, social interactions, and the role of teachers, so that cultural values are understood by students through contextual and meaningful learning experiences in elementary school.